Time-dependent or state-dependent pricing? Evidence from a large currency devaluation episode - Feltrin Junior, Celio (2014)
Two classes of models seek to explain the pattern of price adjustment of firms: models time-dependent and state-dependent. The objective of this work is to raise some empirical evidence in order to distinguishing between the models, i.e. identifying in the way firms actually change price. For this reason, we chose the large devaluation of 1999 as the main tool and analytical environment. The fundamental hypothesis is that the exchange rate shock significantly impacts the cost of some industries, in some cases inducing them to change price after the shock. From a vast base of micro data formed by prices that make up the CPI, some important estimates as the probability and average magnitude of price changes were raised. The magnitude is given by a simple average, while the probability is estimated by the method of maximum likelihood. In the end, the results indicate a behavior of pricing similar to ones proposed by state-dependent models.